Selected aspects of amount relatives: The Romanian-English connection - Grosu, Alexander; Giurgea, Ion (LingBaW. Linguistics Beyond and Within, 2015)
The inter-related goals of this paper are: (i) To contribute to a better understanding of the semantic and morphological properties of amount relatives in Romanian, (ii) to compare and contrast these constructions with their English counterparts, and (iii) to bring into bolder relief than has so far been done in the literature the fact that amount relatives in general are compatible not only with an amount denotation of the complex DPs that contain them, but with an entity denotation as well.